Accuracy and reproducibility of a novel device for monitoring resistance training performed at self-selected movement velocity - Külkamp, W.; Kons, R. L.; de Souza, J.; Kunzler, D. H.; Bishop, C. (Sports Engineering, 2024)
Resistance training does not necessarily require repetition failure, whereas velocity-based training and "training not to failure" are available alternatives to know the optimal point to interrupt the sets. Nevertheless, velocity-based training require exclusively maximal intended velocities and training not to failure currently relies on subjectivity to estimate repetitions in reserve. This study evaluated the accuracy and precision of a linear encoder in estimating the maximum number of repetitions during sets performed until failure at self-selected movement velocity. Fifty-seven males were evaluated in three resistance exercises: close-grip lat pulldown, knee extension, and bench press. Accuracy was evaluated by comparing the mean and median of actual and estimated repetitions using t tests and Wilcoxon signed-rank tests, respectively. Additionally, the fatigue effect in consecutive sets was analyzed using two-way ANOVA for repeated measures. Levels of agreement were assessed through Bland-Altman analysis, and reproducibility was determined by calculating the Intraclass Correlation Coefficient (ICC). The results showed no significant difference between actual and estimated repetitions (t178 = 0.307; p > 0.05; ES = 0.02; Z = - 0.45; p > 0.05; ES = - 0.02), even in the presence of fatigue between consecutive sets. The reproducibility for estimating maximal repetitions was good (ICC3,2 = 0.88 [95% CI = 0.83-0.91], F177,177 = 8.07, p < 0.001), with an acceptable degree of agreement. Errors of less than or equal to two repetitions occurred in over 90% of the series for the close-grip lat pulldown and bench press, with knee extension exhibiting a slightly lower frequency. Hence, practitioners and trainers should consider using this linear encoder for the evaluated exercises, especially when failure is not desired under self-selected velocity conditions.